PENGARUH GOOD CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN (Studi Empiris terhadap Perusahaan Manufaktur Terbuka di Bursa Efek Indonesia tahun 2013) - Zaim Mahbub Budiawan (Jurnal Ilmiah Mahasiswa FEB, 2014)
The aim of this study is to obtain empirical evidence about the influence of Good Corporate Governance and corporate characteristics on dividend policy. Dividend policy proxy for dividend payout ratio (DPR). Good Corporate Governance (GCG) proxy for corporate governance elements include: Transparency, Fairness, Accountability and Responsibility. Characteristics of the company is represented by profitability (ROE), leverage (DER), liquidity (CR), and the size of the company (TA) is used as a control variable to strengthen the influence of Good Corporate Governance on dividend policy (DPR). The sample of this study is go-public manufacturing companies listed in Indonesia Stock Exchange in 2013 period. The methods used in processing the data is multiple linear regression analysis . The results of this study are: ( 1 ) Good Corporate Governance positive influence on dividend policy , it is consistent with the hypothesis made ​​; ( 2 ) the profitability of a positive influence on dividend policy , it is consistent with the hypothesis made ​​; ( 3 ) leverage does not have positive influence on dividend policy , this means that the hypothesis DER has negative influence the DPR is rejected; ( 4 ) Liquidity does not have positive influence on dividend policy , this means that the hypothesis of CR has positive influence on the DPR is rejected; ( 5 ) the size of the company does not have positive influence on dividend policy , this means that the hypothesis that TA has positive influence on the DPR is rejectedKeywords : Dividend Policy (DPR), Good Corporate Governance (GCG), Profitability (ROE), Leverage (DER), Liquidity (CR), Size of the Company (TA).